2015
DOI: 10.1177/0042085915602539
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, Resources, Frustrations, and Empathy: Teachers’ Expectations for Family Involvement for Latino/a ELL Students in Urban STEM Classrooms

Abstract: The importance of family involvement in education is well documented, yet no studies have explored teachers' conceptualization of family involvement for urban English Language Learner (ELL) students in science, technology, engineering, and mathematics (STEM) classrooms. We used an ethnographic approach to investigate middle school STEM educators' perspectives on family involvement for Spanish-speaking ELL students. The analysis revealed that the participants recognized barriers to involvement for families of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…To reiterate, previous research has suggested that perceived barriers of culture and/or language are possible explanations for low engagement and involvement of ELL families (Case, 2015;Wassell, Hawrylak, & Scantlebury, 2015).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…To reiterate, previous research has suggested that perceived barriers of culture and/or language are possible explanations for low engagement and involvement of ELL families (Case, 2015;Wassell, Hawrylak, & Scantlebury, 2015).…”
Section: Resultsmentioning
confidence: 88%
“…This was conducted in order to best understand a holistic perspective of how K-12 administrators are currently engaging and involving ELL students and their families. Previous research had suggested that perceived barriers of culture and/or language are possible explanations for low engagement and involvement of ELL families (Case, 2015;Wassell, Hawrylak, & Scantlebury, 2015).…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
“…Most of the teachers reported desiring better relationships with the students' parents, and Cheyenne -although she admittedly had poor relationships with parents -mitigated her lacking relationships with the parents of ELLs with disabilities by building positive relationships with the students. This finding regarding difficult parent relationships is consistent with Wassell, Hawrylak, and Scantlebury (2017) who also examined the views of teachers who worked with parents of ELL students. They found similar findings which included (a) perceived lack of trust in the school system, (b) communication, and (c) cultural mismatches.…”
Section: Chapter 5 Discussionsupporting
confidence: 86%
“…Parents who are recent immigrants may also be challenged by lack of knowledge of the school culture, feelings of inadequacy, and an all-consuming focus on provision for the family (Cline & Necochea, 2001; Quin & Han, 2014). Teachers may expect them to “step up and be parents” (Wassell, Hawrylak, & Scantlebury, 2015, p. 13) in terms of traditional involvement when hours of necessary employment make them unavailable to their children.…”
Section: Traditional Parent Involvement Policy and Barriers To Parementioning
confidence: 99%